1999
DOI: 10.1007/bf02742346
|View full text |Cite
|
Sign up to set email alerts
|

CT-dichtemessungen zur graduierung subkutaner fibrösen nach photonen-neutronen-therapie maligner speicheldrüsentumoren

Abstract: Fibrosis is correlated with an increasing value of HU of the tissue density in CT. With the described method it is possible to graduate radiation induced subcutaneous fibrosis in correlation to the clinical fibrosis grade according to LENT SOMA. In the patients we examined subcutaneous fibroses after photon/neutron therapy were moderate. Especially in characterising subclinical or slight changes of connective tissue after radiotherapy computed tomography is of value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Poorly differentiated smaller adipocytes show higher attenuation in CT images 18,19 . Tissue inflammation and subsequent fibrosis can also lead to increase the tissue attenuation in CT scans 20 . In a large cohort of patients undergoing cardiac surgery 7 , Antonopoulos et al demonstrated that the average attenuation of adipose tissue is inversely correlated with the expression of adipogenic genes and average adipocyte size, which is driven by intracellular lipid accumulation.…”
Section: %Change In Eat Fat Attenuation In Ct Imagingmentioning
confidence: 99%
“…Poorly differentiated smaller adipocytes show higher attenuation in CT images 18,19 . Tissue inflammation and subsequent fibrosis can also lead to increase the tissue attenuation in CT scans 20 . In a large cohort of patients undergoing cardiac surgery 7 , Antonopoulos et al demonstrated that the average attenuation of adipose tissue is inversely correlated with the expression of adipogenic genes and average adipocyte size, which is driven by intracellular lipid accumulation.…”
Section: %Change In Eat Fat Attenuation In Ct Imagingmentioning
confidence: 99%
“…12 CT images of adipose tissue with larger adipocytes showed lower attenuation because of the increased oil droplet size, 41 while poorly differentiated smaller adipocytes showed higher attenuation on CT images. 42,43 Tissue inflammation and subsequent fibrosis can also increase tissue attenuation on CT. 44 In a large cohort of patients undergoing cardiac surgery, Antonopoulos et al 45 CT imaging with histological findings in each patient. 12 In fact, the percent change in EAT fat attenuation on CT was well correlated with the histologically assessed C/M diameter ratio (Figure 12D).…”
Section: Percent Change In Eat Fat Attenuation Determined By Ct and F...mentioning
confidence: 99%
“…CT images of adipose tissue with larger adipocytes showed lower attenuation because of the increased oil droplet size, 41 while poorly differentiated smaller adipocytes showed higher attenuation on CT images. 42 , 43 Tissue inflammation and subsequent fibrosis can also increase tissue attenuation on CT. 44 In a large cohort of patients undergoing cardiac surgery, Antonopoulos et al 45 demonstrated that the average attenuation of adipose tissue was inversely correlated with adipogenic gene expression and average adipocyte size, which is driven by intracellular lipid accumulation. More recently, Goeller et al 46 showed that the attenuation of peri‐coronary adipose tissue measured by routine CT angiography was related to the progression of non‐calcified plaques.…”
Section: Detection Of Fibrotic Eat Remodeling By Ctmentioning
confidence: 99%
“…Bei 26 Arbeiten (19%; 12%-27%) werden zum Teil Konfidenzintervalle gezeigt, jedoch nicht bei allen Ergebnissen und Grafiken [13, 17, 22, 31, 35, 56, 61, 70-72, 74, 78, 89, 101, 103, 108, 109, 112, 126, 131, 140, 160, 169, 170, 178, 179). Bei 15 Arbeiten (11%; 6%-18%) werden zwar Konfidenzintervalle gezeigt, es wird jedoch nicht immer eindeutig angegeben, um welches Konfidenzintervall es sich dabei handelt [43,45,48,49,60,61,76,86,93,96,135,138,154,155,157].…”
Section: Qualitätsanalyse Der Zeitschrift "Strahlentherapie Und Onkolunclassified